Wages, Sorting on Skill, and the Racial Composition of Jobs - Hirsch, Barry T.; Macpherson, David A. (Journal of Labor Economics, 2004)
Wages for black and white workers are substantially lower in occupations with a high density of black employees, following standard controls. Such correlations can exist absent discrimination or as a result of discrimination. In wage level equations, partial correlations fall sharply after controlling for occupational skills. Longitudinal estimates accounting for worker heterogeneity indicate little wage change associated with changes in racial composition. Results support a “quality sorting” rather than discrimination explanation, with racial density serving as an index of unmeasured skills. Discrimination reflected in racial wage gaps occurs within occupations or across occupations in a manner uncorrelated with racial composition.